PERAN KONSELOR DALAM MENDUKUNG PERKEMBANGAN BELAJAR SISWA MELALUI PENINGKATAN PERILAKU LITERASI DIGITAL - Iki Yusran; Tazkiyatun Nafsih; Muthia Fathina Fadira (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The digital era of 2025 demands significant transformations in the field of education,particularly in enhancing students’ digital literacy skills. Digital literacy encompassesnot only technical competencies but also critical thinking abilities, ethical awareness,and responsible use of digital media. School counselors play a crucial role insupporting students’ learning development through the reinforcement of digitalliteracy behaviors. Therefore, it is essential to examine more deeply the role ofcounselors in fostering students’ digital literacy behaviors and their implications forlearning success. This study employed a literature review design by analyzingvarious scholarly reviews addressing the role of counselors in the digital era. Thefindings indicate that counselors have five primary roles: (1) digital literacyeducators, (2) facilitators of digital learning, (3) consultants on media ethics, (4)psychoeducational guides regarding the impact of social media, and (5) role modelsof healthy digital behavior. These roles contribute to enhancing students’ abilities tosearch for, evaluate, and utilize digital information responsibly, thereby supportingtheir academic achievement and socio-emotional development. The implications ofthis review highlight the need to improve counselors’ digital competencies, integratedigital literacy into guidance and counseling services, and strengthen sustainabletechnology-based educational policies.